Multilocular hydrocephalus - Harold Vasquez; Ezequiel García-Ballestas; Luis Rafael Moscote-Salazar; Sergio A Serrato; William A. Florez Perdomo; Amit Agrawal (Romanian Neurosurgery, 2020)
Multilocular hydrocephalus is an entity that occurs relatively frequently in neurosurgical practice. We are present an editorial letter with a mini-review of the pathophysiology, surgical, and medical treatment.